INOKULASI FUNGI MIKORIZA ARBUSKULA UNTUK MENINGKATKAN PERTUMBUHAN BIBIT KELAPA SAWIT DI PRE NURSERY PADA DOSIS PUPUK NITROGEN YANG BERBEDA - Suprih Wijayani; Herry Wirianata; Anhar Burhanuddin (Program Studi Agroteknologi INSTIPER, 2018)
Fertilizing is an important part in the management of palm oil nursery. The use of nitrogen fertilizer requires special attention because it is closely related to greenhouse gas emission. Alongside the application of sustainability principles at palm oil plantation, the absorption effectivity of nitrogen becomes the main concern to reduce greenhouse gas emission. The symbiosis of arbusculal mycorrhyzal fungi (AMF) becomes an important part to increase the absorption of many nutrition elements as well as reduce the pollution potential. The objective of this research is to understand the role of AMF on the prenursery growth on several intakes of urea fertilizer. The research consists of factorial treatment with several treatments: AMF application frequency: without AMF, AMF application during plantation, and application upon seedling planting and one month after that. The treatment using nitrogen fertilizer consisted of 3 levels: 0, 0.5, and 1.0 gram/seed. Research results showed that AMF application when and one month after seedling planting can increase the prenursery growth of palm oil seed, especially its biomass and the growth of the root. The dosage difference of nitrogen fertilizer caused different seed growths. The 0.5 g/seed dosage tended to result in best oil palm nursery growth compared to other dosages. There is a tendency that the application of nitrogen at 1.0 gram/seed suppressed the AMF colonization at palm oil root growth. Keywords: arbuscular mycorrhyzal fungi, nitrogen fertilizer, palm oil seed, pre nursery